2006
DOI: 10.1086/500510
|View full text |Cite
|
Sign up to set email alerts
|

Stability of CXCL‐8 and Related AU‐Rich mRNAs in the Context of Hepatitis C Virus Replication In Vitro

Abstract: The data suggest that increased CXCL-8 gene expression in the context of HCV replication involves posttranscriptional events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 46 publications
(67 reference statements)
1
23
0
1
Order By: Relevance
“…CXCL-8 mRNA was quantitated by real-time reverse transcriptase (RT)-PCR, as recently described (19). Dilutions of precisely quantitated CXCL-8 cDNA in the PCMGSNEO plasmid (64) (kindly provided by Naofumi Mukaida), ranging from 0 to 10 7 copies per tube, were run in triplicate to generate a standard curve, which served as a reference to calculate the CXCL-8 copy number based on the cycle threshold.…”
Section: Cells and Virusesmentioning
confidence: 99%
See 4 more Smart Citations
“…CXCL-8 mRNA was quantitated by real-time reverse transcriptase (RT)-PCR, as recently described (19). Dilutions of precisely quantitated CXCL-8 cDNA in the PCMGSNEO plasmid (64) (kindly provided by Naofumi Mukaida), ranging from 0 to 10 7 copies per tube, were run in triplicate to generate a standard curve, which served as a reference to calculate the CXCL-8 copy number based on the cycle threshold.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…Furthermore, RIG-N expression was associated with a 2.1-fold increase in the half-life of CXCL-8 mRNA following TNF-␣ stimulation. Statistical comparison of the decay rates by a one-phase exponential model (19) showed that this difference is significant (P ϭ 0.03).…”
mentioning
confidence: 97%
See 3 more Smart Citations